A freeform reflector for a light-emitting diode bicycle head lamp. (August 2016) - Wu, H; Zhang, XM; Ge, P
We propose a freeform reflector for light-emitting diode bicycle head lamps based on a feedback method. The energy relationship between the solid angle of the light-emitting diode source and the target plane is first established. A reflector is then constructed based on non-imaging optics theory and Snell's Law. Feedback modifications are applied in accordance with the deviation between the simulated and the desired light distribution. Then the reflector is regenerated and the deviation is minimized after several iterations. A reflector for a bicycle head lamp is designed for the Cree XP-E LED source whose emitting surface is 1.2 mm × 1.2 mm. Simulation results indicate that the light performance can meet the K-mark regulations. The optical utilization factor can be improved from 73% to 80% and the illuminance uniformity is improved by 22%.